2021
DOI: 10.3390/children8050398
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Trajectory after Invasive Interventions for Patent Ductus Arteriosus of Preterm Infants

Abstract: Invasive interventions have been conducted in preterm infants with significant patent ductus arteriosus (PDA) when medical treatment has failed, and methods of invasive intervention have been reported. Surgical ligation via lateral thoracotomy has been a well-established procedure for decades. Recently, transcatheter occlusion has been safely and feasibly applied to the premature population. However, little research has been conducted on the benefits of transcatheter occlusion in very-low-birth-weight (VLBW) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…1A). Similarly, necrotising enterocolitis (NEC) was reported in 5 studies [14,15,19,27,28] and our study illustrated a comparable baseline characteristic between the TC (n = 31, 13.6%) and SL cohorts (n = 30, 11.6%) (OR = 1.22, 95% CI: 0.20, 7.33, I 2 = 80%) (Fig. 1B).…”
Section: Clinical Characteristicssupporting
confidence: 84%
See 1 more Smart Citation
“…1A). Similarly, necrotising enterocolitis (NEC) was reported in 5 studies [14,15,19,27,28] and our study illustrated a comparable baseline characteristic between the TC (n = 31, 13.6%) and SL cohorts (n = 30, 11.6%) (OR = 1.22, 95% CI: 0.20, 7.33, I 2 = 80%) (Fig. 1B).…”
Section: Clinical Characteristicssupporting
confidence: 84%
“…All 8 studies reported patient comorbidities in both groups (TC: n = 366, SL: n = 390) prior to the procedure. 2 studies [14,28] reported bronchopulmonary dysplasia (BPD) as a pre-procedural comorbidity, with the data showing no difference between the TC group (n = 60, 51.7%) and the SL group (n = 59, 48.4%) (OR = 1.21, 95% CI: 0.71, 2.08, I 2 = 0%) (Fig. 1A).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…In preterm infants with pulmonary hemorrhage and hemodynamically significant PDA who are not able to undergo surgical ligation, some authors have reported transcatheter occlusion as a feasible and alternative approach [ 71 , 72 ]. Less invasive procedures, such as transcatheter closure, may be of use to this critical population [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter PDA occlusion in ELBW infants became technically feasible following the development of a new delivery sheath and device [25]. Recent data show a tendency toward early improvement in the pulmonary score of a transcatheter occlusion group of infants compared with the surgical ligation group [26]. Previously, our group successfully used the umbilical vein for transcatheter closure of the PDA in symptomatic premature infants weighing more than 478 g [8].…”
Section: Discussionmentioning
confidence: 99%